Análisis de las plataformas de exhibición para los Diseñadores de Moda como mecanismo de difusión de sus marcas - Caiza Tapia, Glenda Dayana (2023)
Fashion exhibition and promotion platforms are a mechanism for the dissemination and marketing of both products and services, they are related to consumer systems, their way of acting through consumption and mass culture. The fashion sector is one of the most influenced by what you need to have spaces where you can present your ideas and creations for your business. In the fashion industry, advertising and communication is important to elevate brands. This is why important countries in the world have designed platforms that allow them to connect with trained professionals and consumers worldwide. At the Latin American level, there are platforms that are of great help to brands and fashion designers. Colombiamoda is a very important showcase attended by more than 30,000 attendees who seek to buy, sell and, above all, visualize new trends to apply them to their brands. Also known as Inexmoda, a meeting point where it connects fashion designers with specialized buyers from the value chain of the textile, clothing and fashion industry. A unique space to generate contacts and do business. In Ecuador there are several exhibition platforms for fashion designer brands that seek to create a marketing medium, but they have not been able to take off in the same way as in countries such as Colombia, Perú, México, and Argentina. In the same way, at the local level there are platforms that serve clearly to generate diffusion or commercialization but not both.